Pengaruh Pelatihan Kerja, Disiplin Kerja dan Budaya Kerja Terhadap Kinerja Pegawai Kantor Dinas Kelautan dan Perikanan Provinsi Bengkulu - Waliamin, Janusi; Rahmadani, Muhammad Genta; Fransisko, Reza; Syahbet, Aji Fakhrizal; Azhari, Muhammad Bintang (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2022)
The purpose of this study was to determine how much influence job training, work discipline and work culture had on the performance of the Bengkulu Province Marine and Fisheries Service employees. The variables of this research are job training, work discipline and work culture. The method used in this research is literature study, observation, interviews, and questionnaires. This research is a research with a quantitative approach. The population of this study were all employees of the Bengkulu Province Marine and Fisheries Service, amounting to 70 people with a saturated sample technique. The analytical tool used in this research is SPSS. The data analysis method used is multiple linear regression, multiple correlation, coefficient of determination, t test and f test. Based on the results of the study, it was shown that (1) job training had a significant effect on the performance of the Bengkulu Province Marine and Fisheries Service employees, (2) work discipline had no significant effect on the Bengkulu Province Marine and Fisheries Service employees' performance. marine and fishery service employees (3) work culture has no significant effect on the performance of the Bengkulu province marine and fishery service employees, (4) job training, work discipline, and work culture simultaneously affect the performance of the Bengkulu province marine and fishery service employees.